PENGARUH GREEN LIFE STYLE, FUTURISTIC DESIGN, TECHNOLOGY DAN CONFIDENCE TERHADAP MINAT BELI MOBIL LISTRIK - Shinta Aprika Putri; Ginanjar Rahmawan (Jurnal Kelola: Jurnal Ilmu Sosial, 2022)
This study aims to determine the effect of green life style, futuristic design, technology and confidence on interest in buying electric cars. This research contributes to the development of four wheeled transportation equipment that is environmentally friendly, this is in line with the goals of the Government of Indonesia which continues to make breakthrough efforts to accelerate the growth of the national electric vehicle industry and the world trend towards the use of energy-efficient and environmentally friendly transportation means. The research method used in this research is quantitative method and this research was carried out in the city of Surakarta. The sampling technique used in this study was accidental sampling with a sample size of 90 people. The analysis technique used in this research consists of instrument test, classical assumption test and multiple linear regression test using SPSS version 24.0 for windows. Based on the results of the study, it was found that green life style, futuristic design, technology and confidence had a positive effect on consumer buying interest.